ЭСТЕТИКАЛЫҚ ТӘРБИЯ – ҲӘР ТӘРЕПЛЕМЕ РАЎАЖЛАНҒАН ДӨРЕТИЎШИ ИНСАННЫҢ ҚӘЛИПЛЕСТИРИЛИЎИНИҢ ТИЙКАРЫ - Уразимова, Т.В. (SCIENCE and SOCIETY, 2024)
The article is devoted to the problem of aesthetic education of a person as the basis for the formation of personality. The author reveals the goals and objectives of aesthetic education, considers the most important factors influencing the process of formation and development of a creative personality. Much attention is paid to the role and place of art in the process of aesthetic development of the individual.